91.3k views
3 votes
Convert the function into standard form. Show your work. y-2=-3(x+4)^2

2 Answers

4 votes

Answer:

y = -3x² - 24 x + 50

Explanation:

y - 2 = - 3(x+4)²

y - 2 = -3(x²+8x+16)

y - 2 = -3x² -24x +48

y = -3x² - 24 x + 50

User Jon Olav Vik
by
5.7k points
2 votes

ANSWER

The standard form is

.


y = - 3 {x}^(2) - 24x - 46

EXPLANATION

The given function is


y - 2 = - 3(x + 4)^(2)

The standard form is given by


y =a {x}^(2) + bx + c

We expand to obtain:


y - 2 = - 3( {x}^(2) + 8x + 16)

We expand the parenthesis to obtain:


y - 2 = - 3 {x}^(2) - 24x - 48

Group the similar terms to obtain:


y = - 3 {x}^(2) - 24x - 48 + 2


y = - 3 {x}^(2) - 24x - 46

The standard form is


y = - 3 {x}^(2) - 24x - 46

User Michael Bird
by
5.6k points